THE PROBLEM OF PATIENT-FOCUSED INNOVATION OF TOOTH-TECHNICAL MATERIALS SCIENCE IN THE CONTEXT OF INCREASING THE EFFICIENCY OF THE DENTAL TREATMENT - І.V. Yanіshen; O. L. Fedotov (Ukrainian Medical Stomatological Academy, 2016)
The existing classification of dental materials can only be used in the definition of "associated" selection of dental materials, since in each case the orthopedic treatment of the factors limiting the physician in the selection is the presence in the health care setting of certain dental materials and the individual factors of the patient. So, the dentist-orthopedist in each case of treatment plan takes a decision on "bound" selection of dental materials. The unsolved problem of dental material science is the lack of complient-oriented developments in relation to prosthetic. The list, which can be applied to a specific material, isn't determined by any instruction for use of materials. Solution to this problem is the development and implementation of qualimetrical approach to the assessment of existing and new dental materials with the subsequent formation of the high-level complient complexes. Obtained in the research process, data analysis of 10206 complient systems "materialconstruction" testify to the fact that only by qualimetrics reasonable selection of materials, the level of complient system "materialconstruction", depending on the type of dentures, may rise from 18.2% to 36.5%. By the largest reserves of the improvement is characterized the compliance of materials for the fabrication of immediate dentures - 36.5%, by the lowest - removable orthopedic constructions - 18,2%; compliance of the system "material-construction" in the manufacture of fixed constructions of dentures due to concerted selection of dental materials can be improved by 31.1%. As a result of this work scientific advances for selection of complient complexes of dental materials for the manufacture of specific orthopedic structures, principles and logic of development and the results of clinical application of special selected program of complient system "material-construction," as well as more innovative developments in dental material science were highlighted.